2006
DOI: 10.1128/iai.01187-06
|View full text |Cite
|
Sign up to set email alerts
|

Limited Cross-Reactivity among Domains of the Plasmodium falciparum Clone 3D7 Erythrocyte Membrane Protein 1 Family

Abstract: The var gene-encoded Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) family is responsible for antigenic variation and sequestration of infected erythrocytes during malaria. We have previously grouped the 60 PfEMP1 variants of P. falciparum clone 3D7 into groups A and B/A (category A) and groups B, B/C, and C (category non-A). Expression of category A molecules is associated with severe malaria, and that of category non-A molecules is associated with uncomplicated malaria and asymptomatic infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…47). Parasites expressing group A PfEMP1 proteins occur predominantly among children with limited immunity (7), and IgG to this group of Ags is acquired faster than IgG to other PfEMP1 groups (48,49) and appear to be more cross-reactive (39,50). The data presented in this study underpin these earlier findings and support the hypothesis that IgG to relatively conserved and functionally important Ab epitopes in group A PfEMP1 proteins are of importance in acquisition of clinical immunity to malaria.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…47). Parasites expressing group A PfEMP1 proteins occur predominantly among children with limited immunity (7), and IgG to this group of Ags is acquired faster than IgG to other PfEMP1 groups (48,49) and appear to be more cross-reactive (39,50). The data presented in this study underpin these earlier findings and support the hypothesis that IgG to relatively conserved and functionally important Ab epitopes in group A PfEMP1 proteins are of importance in acquisition of clinical immunity to malaria.…”
Section: Discussionsupporting
confidence: 80%
“…Recombinant ICAM-1-Fc chimera (0.2 mg/well) was added (1 h; room temperature), followed by washing and detection of bound chimera by anti-human HRP-IgG (1:3000 in blocking buffer; 1 h) or by mouse anti-human ICAM-1 (clone RR1/1; AH Diagnostics; 1:400) followed by anti-mouse HRP-IgG (DakoCytomation; 1:1000) (39). In assays of PfEMP1 domain interference of this binding, the ICAM-1-Fc chimera (2 mg/ml) was preincubated with recombinant PfEMP1 constructs (0-50 mg/ml; 1 h; room temperature).…”
Section: Adhesion Of P Falciparum-ie Adhesion To Icam-1mentioning
confidence: 99%
“…Abs to CIDR domains were developed faster than the Abs to DBL domains, and this probably reflects that there is a broader cross-reactivity between CIDR domains than between DBL domains. This notion is supported by previous findings using competition ELISA indicating that different recombinant CIDR domains based on 3D7 sequence could out-compete each other, but that there was little cross-reactivity between 3D7 DBL domains (39). None of the children in this study was likely to have been infected with 3D7, and yet many developed Abs reacting with recombinant DBL domains based on this genome.…”
Section: Discussionsupporting
confidence: 76%
“…It has previously been suggested that such exchange is more likely to take place between groups B and C PfEMP1, but that some characteristics of group A PfEMP1 have leaked into these two groups (10). Based on the present and previous studies (24,29), we speculate certain PfEMP1 domains (e.g., CIDR) to be more likely exchanged and conserved than others and thus to contribute to the VSA SM phenotype of parasites causing severe malaria in individuals with little or no immunity. Such conservation and exchange of certain domains would explain the discrepancy between the results presented here and those previously seen in comparison between severe and uncomplicated malaria (13), because for a significant finding to occur, severe malaria-type domains and not full-length PfEMP1 would need to be identified before testing of a much larger number of different domain types and would probably also require a larger set of plasma samples from different individuals.…”
Section: Discussionmentioning
confidence: 99%